2013
DOI: 10.1002/app.39792
|View full text |Cite
|
Sign up to set email alerts
|

Double‐hydrophilic polyether antiscalant used as a crystal growth modifier of calcium scales in cooling‐water systems

Abstract: In this study, we synthesized a novel double-hydrophilic poly(ethylene glycol) (PEG)-based crystal growth modifier polyethylene glycol double-ester of maleic anhydride/acrylic acid named PEGDMA/AA, whose structure was still linear but also had some differences from a traditional chelating linear polymer, in which the PEG segment was incorporated. The scale inhibition behavior of PEGDMA/AA was evaluated by means of a static scale inhibition method. As the polymerization degree of PEG n DMA was 8 (n 5 8), the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
3
10
1
Order By: Relevance
“…Polyethylene glycol (PEG) is an innoxious [21][22][23], neutral and nonionic surface active agent with the hydrophilic groups (-OH and -O-) and hydrophobic group (-CH 2 -CH 2 -) [24]. The effects of PEG on the nucleation and crystal growth of CaCO 3 have attracted scientists interested in scale inhibitor research [25,26]. However, single composition of β-CD or PEG used as a scale inhibitor barely achieves the desired anti-scaling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is an innoxious [21][22][23], neutral and nonionic surface active agent with the hydrophilic groups (-OH and -O-) and hydrophobic group (-CH 2 -CH 2 -) [24]. The effects of PEG on the nucleation and crystal growth of CaCO 3 have attracted scientists interested in scale inhibitor research [25,26]. However, single composition of β-CD or PEG used as a scale inhibitor barely achieves the desired anti-scaling effect.…”
Section: Introductionmentioning
confidence: 99%
“…The stretching vibration peak of C S in the sulfonic acid group is 621 cm −1 , the symmetrical stretching vibration absorption peak of S O is 1170 cm −1 , and the stretching vibration absorption peak of the amide II band (including N H) is 1573 cm −1 . 10,26,34 It indicates that the optimal concentration of P(MA-AA-AMPS) is 20 mg L −1 , and the scale inhibition efficiency is significantly improved compared with the commercial P(AA) and P(MA-co-AA). 32 Table I shows the molecular weight and its distribution of P(MA-AA-AMPS) synthesized under different monomer ratios, which were tested by gel permeation chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…27,31 In addition, the molecular-weight distribution index indicated that the molecular-weight distribution of the scale inhibitor synthesized in this work was relatively uniform. 6,34 However, the carboxylic acid group alone is not conducive to improving the scale inhibition efficiency. At the dosage of 2-14 mg L −1 , the scale inhibition effect increases rapidly with the increase in the concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations